Sosial Ekonomi Masyarakat Madura Abad 19-20: Sebuah Kajian Ekologi Sejarah - Mohammad Refi Omar Ar Razy; Dade Mahzuni (Jurnal Siginjai, 2021)
This study aims to analyze the concept of Madurese culture in the context of settlement and agriculture. The Madurese community is an agrarian society originating from the island of Madura with the dominant characteristic of using the Madurese language. Today, the Madurese are famous for the habit of people who often migrate outside the island of Madura, this is done solely to meet the economic needs of the Madurese. Many factors affect the migration activity, but the most dominant is that on the island of Madura the land is not fertile so that the Natural Resources in Madura are not well developed, especially in the agricultural sector. Even so, the Madurese have the concept of living and farming. In the concept of living it is known as the Tanean Lanjheng, while in the agricultural system it is known as the Moor Ecological system. This study uses a historical method approach consisting of heuristics, criticism, interpretation and historiography. Therefore, in this study, it is known: 1) Ecological systems in the agricultural system on the island of Madura, 2) The housing ecology system of the Madurese community, and 3) Implications of the agricultural and housing system on the socio-economy community of Madura.